Zirconium oxide implant surface modification treatment system and transparent electrode preparation method

By designing a zirconia implant surface modification treatment system containing glass tubes, transparent electrodes and rod-shaped electrodes, the plasma is excited by blocking discharge with low-pressure medium, the problems of restricted use scenarios and poor processing effects of traditional systems are solved, and efficient and low-cost implant surface modification treatment is achieved.

CN119560358AInactive Publication Date: 2025-03-04SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411720468.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The traditional zirconia implant surface modification treatment system has the need for limited use scenarios, difficulty in visual presentation, poor processing effect, high cost and inability to meet the needs of immediate processing.

Method used

A zirconia implant surface modification treatment system was designed, including glass tubes, pneumatic joints, vacuum pumps, transparent electrodes and rod-shaped electrodes. The plasma was excited by blocking discharge of low-pressure medium to realize the surface modification treatment of implants.

Benefits of technology

The system can efficiently process zirconia implants in desktop-level usage scenarios, reduce processing costs, realize real-time monitoring and closed-loop control, and meet the needs of doctors for immediate processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560358A_ABST
    Figure CN119560358A_ABST
Patent Text Reader

Abstract

According to the zirconia implant surface modification treatment system and the transparent electrode preparation method, the upper end of a glass tube of the system is connected with a pneumatic connector, and the pneumatic connector is connected with a vacuum pump through a pipeline; the transparent electrode is sprayed on the outer wall of the glass tube; the rod-shaped electrode is fixed in the center of the inner side of the lower end of the glass tube; the zirconium oxide implant is inversely arranged above the rod-shaped electrode and is tightly attached to the rod-shaped electrode; the spraying area of the transparent electrode on the outer side of the glass tube completely wraps the zirconium oxide implant, and the spraying area of the transparent electrode on the outer side of the glass tube further wraps a rod-shaped electrode with a preset length; the transparent electrode is electrically connected with a low-voltage electrode of the plasma power supply, the rod-shaped electrode is electrically connected with a high-voltage electrode of the plasma power supply, and the plasma power supply excites plasmas through the transparent electrode and the rod-shaped electrode so as to modify the surface of the zirconium oxide implant. According to the method, the problems of limited use scene, difficulty in visual presentation, poor processing effect, high cost and incapability of meeting immediate processing in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dental implants, and in particular relates to a surface modification treatment system for a zirconium oxide implant and a transparent electrode preparation method. Background Art

[0002] At present, dental implants are an important means to improve the life experience of patients with missing teeth, and implants are a key component.

[0003] At present, there are various materials and surface treatment processes for implants, and most of the implants that are being maturely applied are titanium implants. Common treatment methods include: sandblasting acid etching, ultraviolet light irradiation, surface coating plasma treatment, etc. Correspondingly, traditional implant surface hydrophilic modification devices can only treat titanium implants. Due to the different physical and chemical properties of titanium and zirconia, although there are other hydrophilic modification devices or methods for zirconia materials, they are not effective or the cost is too high when treating zirconia implants with complex shapes. The traditional use of plasma as a related device for treating implants has the following problems:

[0004] ① It is necessary to use rare gas as the working gas to excite plasma, the processing cost is too high and the device size is large, and the usage scenarios are limited. ② Because the electrode that excites plasma covers the implant treatment area, it is impossible to monitor the treatment process in real time and close the loop. ③ Because the treatment process cannot be intuitively visualized, doctors and patients have a strong distrust of the implant treatment results. ④ Because plasma requires high-frequency and high-voltage alternating current, common transparent electrode materials cannot produce plasma due to substandard electrical properties or their performance is severely degraded after long-term use. ⑤ Transparent electrode materials that can excite plasma are too expensive and the manufacturing process is complicated. ⑥ The processing temperature of some treatment devices is too high, and the implant needs to be cooled for a long time after treatment. It cannot meet the doctor's needs for immediate treatment at the chair before surgery. Summary of the invention

[0005] To this end, the present invention provides a zirconia implant surface modification treatment system and a transparent electrode preparation method to solve the problems of traditional technologies such as limited usage scenarios, difficulty in visual presentation, poor treatment effect, high cost, and inability to meet immediate treatment requirements.

[0006] In order to achieve the above-mentioned object, the present invention provides the following technical solutions: a zirconia implant surface modification treatment system, comprising a glass tube, a pneumatic joint, a vacuum pump, a transparent electrode, a rod-shaped electrode and a plasma power supply;

[0007] The upper end of the glass tube is connected to the pneumatic joint, and the pneumatic joint is connected to the vacuum pump through a pipeline, and the vacuum pump is used to adjust the working air pressure inside the glass tube; a zirconium oxide implant is arranged inside the glass tube;

[0008] The transparent electrode is sprayed on the outer wall of the glass tube, and the rod-shaped electrode is fixed on the inner center of the lower end of the glass tube; the zirconia implant is inverted above the rod-shaped electrode and is closely attached to the rod-shaped electrode;

[0009] The transparent electrode completely wraps the zirconia implant in the spraying area outside the glass tube, and the transparent electrode also wraps the rod-shaped electrode of a preset length in the spraying area outside the glass tube;

[0010] The transparent electrode is electrically connected to the low voltage pole of the plasma power supply, the rod-shaped electrode is electrically connected to the high voltage pole of the plasma power supply, and the plasma power supply excites plasma through the transparent electrode and the rod-shaped electrode to modify the surface of the zirconia implant.

[0011] As a preferred solution of the surface modification treatment system of zirconium oxide implants, the material of the glass tube is quartz glass with a dielectric constant of 4-20;

[0012] The length of the glass tube is 5-15 cm, the inner diameter of the glass tube is 4-6 mm, and the thickness of the glass tube is 1-3 mm.

[0013] As a preferred solution of the surface modification treatment system of zirconium oxide implants, a first conductive ring is provided at the electrical connection between the transparent electrode and the low-voltage pole of the plasma power supply, and the center of the first conductive ring coincides with the center of the top end of the transparent electrode;

[0014] A second conductive ring is provided at the electrical connection between the transparent electrode and the high voltage pole of the plasma power supply, and the outer side of the second conductive ring is sealed and insulated with silicone rubber and polytetrafluoroethylene materials.

[0015] As a preferred solution for the surface modification treatment system of zirconia implants, the transparent electrode is an electrode made of nano silver wires and liquid metal covered with PMMA / PS / PC transparent insulating materials.

[0016] As a preferred solution of the surface modification treatment system of zirconium oxide implants, the rod-shaped electrode adopts a copper column, the diameter of the rod-shaped electrode is 1-5 mm, and the length of the rod-shaped electrode is 5-50 mm.

[0017] As a preferred solution of the zirconia implant surface modification system, a first distance between the top end of the rod-shaped electrode and the bottom end of the glass tube is greater than a second distance between the bottom end of the transparent electrode and the bottom end of the glass tube.

[0018] As a preferred solution of the zirconia implant surface modification treatment system, the working air pressure of the vacuum pump is -80 to -100 kPa, and a vacuum gauge is connected to the pipeline between the pneumatic joint and the vacuum pump, and the vacuum gauge is used to indicate the working air pressure inside the glass tube;

[0019] The output frequency of the plasma power supply is 0-100kHz, and the output voltage peak value of the plasma power supply is 1-10kV.

[0020] The present invention also provides a method for preparing a transparent electrode of a zirconium oxide implant surface modification system, comprising the following steps:

[0021] cleaning the glass substrate using a washing liquid;

[0022] Using plasma to perform jet treatment on the cleaned glass substrate;

[0023] Prepare a nano silver wire raw material solution, wherein the diameter of the nano silver wire in the nano silver wire raw material solution is 40-300nm; the length of the nano silver wire in the nano silver wire raw material solution is 10-200μm; the concentration of the nano silver wire raw material solution is 5-20mg / ml; dilute the nano silver wire raw material solution to a concentration range of 0-10mg / ml;

[0024] Spraying the diluted silver nanowire raw material solution onto the glass substrate after the jet treatment;

[0025] Performing plasma jet treatment on the nano silver wire layer on the glass substrate after spraying the nano silver wire raw material solution;

[0026] preparing a liquid metal solution, diluting the liquid metal raw material in the solution to 0-3 mg / ml, and subjecting the diluted liquid metal solution to ultrasonic mixing;

[0027] Spraying the diluted liquid metal solution onto the nano silver wire layer on the glass substrate after the plasma jet treatment;

[0028] The glass substrate sprayed with the diluted liquid metal solution is placed upside down above the liquid surface of an open container containing hydrochloric acid for treatment, and after treatment, the glass substrate is placed in a drying oven for drying to form an electrode;

[0029] A transparent protective material for a circuit board is sprayed onto the electrode on the surface of the dried glass substrate, and the sprayed transparent protective material for the circuit board is dried to form a transparent electrode.

[0030] As a preferred solution for the preparation of transparent electrodes for the surface modification treatment system of zirconium oxide implants, the liquid metal uses gallium-indium alloy; the liquid metal element ratio of gallium:indium = 0:1-1:0; the dilution solution of the liquid metal raw material uses isopropanol; the amount of the sprayed liquid metal solution is 0-1ml / cm 2 .

[0031] As a preferred solution of the method for preparing a transparent electrode for a surface modification treatment system of a zirconium oxide implant, the concentration of the hydrochloric acid is 0-50%, and the treatment time is 0-30s; the distance between the electrode and the hydrochloric acid liquid surface during the hydrochloric acid treatment is 0-10cm; the drying temperature after the hydrochloric acid treatment is 0-100°C, and the drying time is 0-10h;

[0032] The transparent protective material of the circuit board adopts PMMA / PS / PC transparent insulating material.

[0033] The present invention has the following advantages:

[0034] The present invention excites plasma by reducing the gas pressure, so that the processing system can directly excite the air in the glass tube to generate plasma, without the need for additional gas cylinders, greatly reducing the hardware size, and broadening the use scenario to the desktop level; no rare gas is required as a working gas, which can greatly reduce the processing cost; because the total amount of gas excited in the glass tube decreases after the gas pressure is reduced, the power required to excite the gas is reduced, and the processing temperature is greatly reduced to room temperature level, without the need for additional heat dissipation, meeting the doctor's needs for immediate treatment at the chairside before surgery.

[0035] The present invention forms a "needle-ring" electrode structure by using a transparent electrode and a rod-shaped electrode, and adjusts the position parameters and size parameters of the two electrodes so that the transparent electrode as a "ring" and the rod-shaped electrode as a "needle" cooperate with each other, thereby directly exciting plasma without using a metal implant as an electrode to excite the implant like in traditional devices, thereby being able to process zirconia implants and other related non-metallic materials for dental use; by completely wrapping the implant between the two electrodes, the generated plasma can more evenly cover the entire implant, thereby achieving a better treatment effect.

[0036] The present invention solves the problem that conventional transparent electrode materials cannot generate plasma due to substandard electrical properties or their performance deteriorates severely after long-term use. It can generate plasma stably for a long time under working conditions. Due to the transparency of the transparent electrode, relevant parameters can be monitored in real time during the generation of plasma. By using detection means such as spectrometers and infrared thermal imagers, plasma active substances, device temperature and other data can be detected in real time during the hydrophilic activation treatment. Closed-loop control is performed while ensuring thermal safety, and electrical parameters are adjusted in real time to ultimately obtain the optimal parameters. The treatment process is intuitively and visually presented, which minimizes the distrust of doctors and patients in implant treatment. The transparent electrode manufacturing process is simple and the manufacturing cost is extremely low.

[0037] The transparent electrode of the present invention is sprayed on the outside of the glass tube, and its function is to connect with the low-voltage pole of the power supply and generate plasma as a low-voltage pole. The position and size of the transparent electrode are closer to the rod-shaped "needle" electrode than the existing device, and even partially overlap. It is helpful to excite plasma with lower power, and at the same time, the generated plasma can completely cover the implant.

[0038] The present invention increases the diameter of the "needle" type rod-shaped electrode to be larger than the diameter of the implant, thereby ensuring that the range of plasma generation can cover the threaded portion of the implant side. The air gap distance between the outer side of the electrode and the inner side of the glass tube can be reduced, thereby increasing the excitation intensity. By increasing the coaxiality between the rod-shaped electrode and the glass tube, the plasma generated by excitation in the glass tube can be made as uniform as possible. The distance between the top end of the rod-shaped electrode and the bottom end of the glass tube needs to be greater than the distance between the bottom end of the transparent electrode and the bottom end of the glass tube. Reducing the distance between the two electrodes reduces the electrical parameters (such as power and voltage) required to excite and maintain the plasma, thereby helping to reduce the temperature of the device and the implant and extending the service life of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0040] Figure 1 A schematic diagram of a surface modification treatment system for a zirconium oxide implant provided in an embodiment of the present invention;

[0041] Figure 2 This is a schematic diagram of the peripheral structure of the glass tube of the zirconia implant surface modification system provided in an embodiment of the present invention.

[0042] In the figure, 1. glass tube; 2. pneumatic joint; 3. vacuum pump; 4. transparent electrode; 5. rod-shaped electrode; 6. plasma power supply; 7. first conductive ring; 8. second conductive ring; 9. vacuum gauge. DETAILED DESCRIPTION

[0043] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] See also Figure 1 and Figure 2 , an embodiment of the present invention provides a zirconia implant surface modification treatment system, comprising a glass tube 1, a pneumatic joint 2, a vacuum pump 3, a transparent electrode 4, a rod-shaped electrode 5 and a plasma power supply 6;

[0046] The upper end of the glass tube 1 is connected to the pneumatic joint 2, and the pneumatic joint 2 is connected to the vacuum pump 3 through a pipeline, and the vacuum pump 3 is used to adjust the working air pressure inside the glass tube 1; a zirconia implant is arranged inside the glass tube 1;

[0047] The transparent electrode 4 is sprayed on the outer wall of the glass tube 1, and the rod-shaped electrode 5 is fixed at the inner center of the lower end of the glass tube 1; the zirconia implant is inverted above the rod-shaped electrode 5 and is close to the rod-shaped electrode 5;

[0048] The transparent electrode 4 completely wraps the zirconia implant in the spraying area outside the glass tube 1, and the transparent electrode 4 also wraps the rod-shaped electrode 5 of a preset length in the spraying area outside the glass tube 1;

[0049] The transparent electrode 4 is electrically connected to the low voltage pole of the plasma power supply 6, and the rod-shaped electrode 5 is electrically connected to the high voltage pole of the plasma power supply 6. The plasma power supply 6 excites plasma through the transparent electrode 4 and the rod-shaped electrode 5 to modify the surface of the zirconia implant.

[0050] In this embodiment, the interior of the quartz glass tube 1 is the core area for generating plasma, and the principle of generating plasma in the glass tube 1 is low-pressure dielectric barrier discharge. In low-pressure dielectric barrier discharge, the smaller the air gap spacing, the easier it is for discharge plasma to occur, and the easier it is to obtain plasma with uniform spatial distribution. In low-pressure dielectric barrier discharge, for different materials, when the gas gap and the applied voltage remain unchanged, the discharge intensity increases with the increase of the dielectric constant; for the same material, when the applied voltage remains unchanged, the discharge intensity decreases with the increase of its thickness. Therefore, in order to obtain a stronger dielectric barrier discharge, a material with a larger dielectric constant and a thinner thickness should be selected. In addition, the bottom of the glass tube 1 needs to take into account both sealing and insulation.

[0051] Among them, the optimal design principle of the glass tube 1 is that in terms of material: a glass material with a dielectric constant as large as possible should be selected, and in terms of size: under the premise that the implant can be accommodated in the glass tube 1, the glass tube 1 should be as small as possible, which is reflected in: the gap between the implant and the inner wall of the glass tube 1 needs to be as small as possible, and the wall of the glass tube 1 is as thin as possible, and cannot be too thin to ensure electrical safety. In addition, in order to ensure the uniformity of plasma excitation, the distance between the top of the implant and the top of the first conductive ring 7 at the top of the transparent electrode 4 is as small as possible, that is, the glass tube 1 should have a certain length.

[0052] In dielectric barrier discharge plasma, for different dielectric materials, when the gas gap and the applied voltage remain unchanged, the discharge intensity increases with the increase of the dielectric constant of the dielectric. The greater the discharge intensity, the stronger the plasma excitation. In order to obtain a better plasma excitation effect, a material with a larger dielectric constant should be selected. Quartz glass is a common transparent dielectric material with a larger dielectric constant, and its electrical properties are stable and high temperature resistant. Therefore, the material of the glass tube 1 is quartz glass with a dielectric constant of 4-20, preferably 5, that is, ordinary quartz glass.

[0053] To ensure uniformity of plasma excitation, the distance between the top of the implant and the top of the conductive ring at the top of the transparent electrode 4 is as small as possible, that is, the glass tube 1 should have a certain length. Therefore, the length of the glass tube 1 is 5-15 cm, preferably 10 cm.

[0054] In this embodiment, in the low-pressure dielectric barrier discharge, the smaller the air gap spacing, the easier it is to excite the plasma, and the easier it is to obtain a plasma with uniform spatial distribution. The size of the air gap between the inner wall of the glass tube 1 and the outer side of the implant can be controlled by the inner diameter of the glass tube 1. The inner diameter of the glass tube 1 should be larger than the outer diameter of a common implant. The outer diameter of a common implant is 4 mm. 4-6 mm is the inner diameter range that can excite plasma (i.e., the air gap is 0.5-1 mm).

[0055] In dielectric barrier discharge plasma, for the same dielectric material, when the applied voltage remains unchanged, the discharge intensity decreases as its thickness increases. Therefore, the dielectric thickness should be as small as possible while ensuring mechanical strength. 1-3mm is the preferred thickness of the glass tube 1. A too thin glass tube 1 is fragile, and a too thick glass tube 1 has a poor plasma excitation effect.

[0056] In this embodiment, a first conductive ring 7 is provided at the electrical connection between the transparent electrode 4 and the low-voltage pole of the plasma power supply 6, and the center of the first conductive ring 7 coincides with the center of the top of the transparent electrode 4; a second conductive ring 8 is provided at the electrical connection between the transparent electrode 4 and the high-voltage pole of the plasma power supply 6, and the outer side of the second conductive ring 8 is sealed and insulated with silicone rubber and polytetrafluoroethylene materials.

[0057] Specifically, the transparent electrode 4 is connected to the low-voltage pole of the plasma power supply 6 by using the first conductive ring 7 at the top position of the transparent electrode 4, and the liquid metal is evenly applied at the contact position between the first conductive ring 7 and the transparent electrode 4 to reduce the contact resistance. Since the first conductive ring 7 is opaque and its resistance is much lower than that of the transparent electrode 4, its position should be as far away as possible from the rod-shaped electrode 5 connected to the positive pole of the plasma power supply 6 to avoid blocking the implant or affecting the discharge. To ensure the stability of the connection, the top of the transparent electrode 4 coincides with the center of the first conductive ring 7. And the liquid metal is evenly applied at the contact position between the first conductive ring 7 and the transparent electrode 4 to reduce the contact resistance.

[0058] Among them, the second conductive ring 8 at the lower end of the glass tube 1 is fixed to the center of the inner side of the glass tube 1. When the implant is treated, it is inverted above the high-voltage electrode in the tube and close to the electrode. The lead wire of the second conductive ring 8 is connected to the high-voltage pole of the plasma power supply 6. At the same time, silicone rubber and polytetrafluoroethylene materials are used on the outside of the second conductive ring 8 for sealing and insulation. The preferred dielectric constant is 2.8, the dielectric strength is ≥20kV / mm, and the volume resistance is 2×10 15 Ω.cm silicone rubber.

[0059] In this embodiment, the pneumatic connector 2 is used to connect the upper end of the glass tube 1 with the pipeline leading to the vacuum pump 3. When the implant is disconnected from the glass tube 1, the implant is placed into the glass tube 1 from the side where the pneumatic connector 2 is located.

[0060] In this embodiment, the transparent electrode 4 is used as the "ring" outer electrode of the "needle-ring" type coaxial dielectric barrier discharge, and the transparent electrode 4 is sprayed on the outside of the glass tube 1. Its function is to connect with the low-voltage pole of the power supply and generate plasma as a low-voltage pole. In order to ensure that the plasma generated in the glass tube 1 can completely cover the implant, the spray position of the transparent electrode 4 on the outside of the glass tube 1 needs to completely cover the implant and part of the rod-shaped electrode 5.

[0061] Specifically, the specific materials are prepared as follows:

[0062] a1) Silver nanowire (Nanjing Xianfeng Nano), with a diameter of 0-50 nm, a length of 100-150 μm, a concentration of 10 mg ml-1, a PVP molecular weight of 58,000, provided in the form of an isopropanol suspension;

[0063] a2) Liquid metal (Dongguan Huatai Metal Materials Technology Co., Ltd.), gallium-indium alloy (gallium 75% / indium 25%);

[0064] a3) Isopropanol (McLean's reagent);

[0065] a4) Hydrochloric acid (Chengdu Kelong Chemical Co., Ltd.), mass percentage is 36%-38%.

[0066] a5) Transparent protective varnish (PLASTIK, Cramolin).

[0067] The specific preparation process is as follows:

[0068] First, the liquid metal (60 mg) was dispersed in 20 ml of isopropanol and then ultrasonically disrupted at 600 W for 20 min. A gray suspension was obtained after ultrasonic disruption and further diluted with isopropanol to 1 mg ml -1 .

[0069] Second, 5 ml of the solution was concentrated to 0.5 mg ml -1 The nano silver wires are evenly sprayed on the side of the glass tube 1 at a position 12-50 mm away from the bottom end using a common spray gun with nitrogen as the carrier gas.

[0070] Third, 2 ml of the diluted liquid metal suspension was evenly sprayed on the silver nanowire network.

[0071] Fourth, the glass tube 1 was placed 1 cm above a petri dish containing HCl solution (36-38 wt%) and slowly rotated to allow the hydrochloric acid vapor to evenly treat the liquid metal, and then dried in a controlled drying oven at 35° C. for 4 hours to effectively remove any residual moisture and hydrochloric acid.

[0072] Fifth, a first conductive ring 7 is used at the top of the transparent electrode 4 to connect the transparent electrode 4 with the low voltage pole of the power supply, and liquid metal is evenly applied at the contact position between the first conductive ring 7 and the transparent electrode 4 to reduce the contact resistance.

[0073] Sixth, under the condition that the ambient humidity is not higher than 60%, the transparent protective insulating material is sprayed uniformly on the transparent electrode 4 and the first conductive ring 7, and then dried in a controllable drying oven at 60° C. for 12 hours.

[0074] Among them, the protection range and preferred value of each parameter are:

[0075] b1. [The upper limit of the diameter of the nanosilver wire in the nanosilver wire raw material solution is 40-300nm, preferably 50nm; the length is 10-200μm, preferably 100-150μm; the core is to use nanowires with a large aspect ratio]. Reason: After being sprayed onto the outer wall of the glass tube 1, the nanosilver wires will randomly overlap with each other to form a nanosilver wire grid. The nanosilver wire grid is the bottom layer of the transparent electrode 4. The larger the aspect ratio (length) to diameter (diameter) (i.e., the thinner), the more overlaps there are between the nanosilver wires, and the denser the grid formed. On the one hand, a dense nanosilver wire network can withstand greater electrical parameters without failure; on the other hand, a dense grid helps the liquid metal to penetrate into the grid evenly after hydrochloric acid treatment. The more evenly the liquid metal penetrates into the nanosilver wire grid, the greater the electrical parameters that the grid can withstand. The larger the electrical parameters, the better the plasma excitation effect.

[0076] b2. [Types of dispersants for silver nanowires: water / ethanol / isopropanol, preferably isopropanol]. Reason: Water / ethanol / isopropanol are all common dispersants for nanomaterials, which can improve the interaction between solid particles and liquids, making it difficult for particles to aggregate, thereby achieving the purpose of maintaining the dispersed state of particles. Isopropanol has the best dispersing effect.

[0077] b3. [Concentration of the raw material solution of nano silver wire: 5-20 mg / ml, preferably 10 mg / ml]. Reason: The initial concentration of materials provided by different manufacturers is different, but since they all need to be diluted before use, the initial concentration value is not very important. 5-20 mg / ml is the concentration of common commercial raw materials.

[0078] b4. [Optimal concentration range of diluted nanosilver wire: 0-10mg / ml, preferably 0.5mg / ml]. Reason: The reasons for controlling the concentration of the nanosilver wire dilution solution are: ① If the concentration is too low, the total amount of solution required for spraying is too much, which takes too long. It may also affect the overlap between the nanosilver wires, making the overlap loose or reducing the number of overlap points, thereby reducing the density of the nanosilver wire grid. ② If the concentration is too high, it is easy to clog the spray gun and reduce the spray quality. In addition, the nanosilver wires may condense with each other and cannot form a nanosilver wire grid. 0-10mg / ml is the best range for ordinary spray gun spraying after experimental testing.

[0079] b5. [Transfer method: spraying / spin coating / deposition / magnetron sputtering, etc., preferably ordinary spray gun spraying]. Reason: The advantage of ordinary spray gun manual spraying is the lowest processing cost and easy to implement, while the disadvantage is the highest requirement for solution configuration. By optimizing the configuration of nano silver wires so that it can be applied to ordinary spray gun spraying, which has the highest requirements for solution configuration, other transfer methods with lower requirements for solution preparation can be realized. Spraying / spin coating / deposition / magnetron sputtering, etc. are common process methods for producing thin film materials in the industrial field.

[0080] b6. [If you choose to spray with a common spray gun, you need to control the type of spray carrier gas (nitrogen or compressed air) / pressure (0-10bar), preferably nitrogen (anti-oxidation nanosilver wire) / pressure 4bar]. Reason: The main principle for selecting the type of spray carrier gas is to prevent the carrier gas from oxidizing the nanosilver wire. The main principle for selecting the spray carrier gas pressure is: too high a carrier gas pressure may cause the carrier gas to blow away the nanosilver wire that has been attached to the substrate, and it is difficult to control; too low a carrier gas pressure is not conducive to the smooth spraying of the nanosilver wire.

[0081] b7. [Spraying speed: The spraying speed is difficult to quantify due to manual operation. It is preferred to spray the nanosilver wire solution in a mist form, and after spraying it onto the substrate, the solution can evaporate and dry immediately without leaving any liquid stains]. Reason: If the spraying speed is too fast, the nanosilver wire may not adhere firmly. If the spraying speed is too slow, the carrier gas may blow away the nanosilver wire that has been attached to the substrate, and if the spraying speed is too slow, the nanosilver wire solution may not evaporate in time, making it difficult for the nanosilver wire to adhere to the target position of the substrate.

[0082] b8.

Spraying nano silver wire solution volume: 0-1ml / cm 2 , preferably 0.5 ml / cm 2

[0083] b9. [Spraying position: 8-80mm from the bottom end of the side of the glass tube 1, preferably 12-50mm from the bottom end of the side of the glass tube 1 (according to the size of the implant and the coordination of the rod-shaped electrode 5)]. Reason: The nanosilver wire is the bottom layer of the transparent electrode 4, and its position is the position of the transparent electrode 4. Since the position of the transparent electrode 4 needs to be determined in coordination with the size and position of the rod-shaped electrode 5 according to the size of the implant. Therefore, the spraying position of the transparent electrode 4 must also meet the requirement of completely wrapping the implant and part of the rod-shaped electrode 5 on the outside of the glass tube 1. 12-50mm from the bottom end is the optimal range that meets the requirement of completely wrapping the implant and part of the rod-shaped electrode 5 on the outside of the glass tube 1 after experimental testing.

[0084] b10. [Type of liquid metal: gallium / indium or its alloy, preferably gallium-indium alloy with a ratio of gallium:indium=3:1]. Reason: Common liquid metals will exist in the form of small particles (diameter 1-2μm) when sprayed onto the nanosilver wire grid. After being crushed with hydrochloric acid vapor, they can smoothly penetrate into the nanosilver wire grid to form a hybrid conductive network. The liquid metal penetrates into the nanosilver wire grid, further reducing the resistance of the nanosilver wire grid, enhancing the mechanical strength of the nanosilver wire grid, and improving the adhesion of the nanosilver wire grid to the substrate material, ultimately better exciting plasma. The gallium-indium alloy with a ratio of gallium:indium=3:1 has a more obvious improvement in conductivity.

[0085] b11. [The optimal concentration range of liquid metal diluent: 0-3mg / ml, preferably 1mg / ml]. Reason: The concentration of liquid metal diluent reflects the size distribution relationship of liquid metal particles in the diluent to a certain extent. The higher the concentration, the larger the liquid metal particles are, and vice versa. After the nanosilver wire grid is crushed by hydrochloric acid, the overly large liquid metal particles penetrate into the nanosilver wire grid, making the hybrid conductive grid too thick and reducing the transparency; the overly small liquid metal particles cannot completely fill the nanosilver wire grid and cannot effectively improve the conductivity of the hybrid grid. 0-3mg / ml is the optimal range after experimental testing.

[0086] b12.

Liquid metal spraying amount: 0-1ml / cm 2 , preferably 0.2 ml / cm 2

[0087] b13. [Hydrochloric acid concentration: 0-50%, preferably 36%-38%].

[0088] b14. [Hydrochloric acid vapor treatment time 0-30s, preferably 10s].

[0089] b15. [During hydrochloric acid treatment, the distance between the electrode and the hydrochloric acid liquid surface is 0-10 cm, preferably 1 cm].

[0090] b16. [Hydrochloric acid drying temperature 0-100°C, preferably 35°C].

[0091] b17. [Hydrochloric acid drying time 0-10h, preferably 4h]. Reason: The main purpose of hydrochloric acid treatment is to break the oxide film formed on the surface of the liquid metal particles so that the liquid metal can smoothly penetrate into the nano silver wire grid. If the degree of hydrochloric acid vapor treatment is insufficient, the liquid metal particles will not be completely broken, the liquid metal will not fully penetrate into the nano silver wire grid, and the conductivity of the transparent electrode 4 will be insufficient. If the degree of hydrochloric acid vapor treatment is too high or the hydrochloric acid is not completely dried and there are residues, HCl may react with the nano silver wires to form insulating silver chloride aggregates, which will eventually cause the nano silver wires to break, increase the resistance of the transparent electrode 4, and deteriorate the conductivity.

[0092] b18. [Conductive ring width: 0-15 mm, preferably 10 mm]. Reason: As a connecting component connecting the transparent electrode 4 and the low-voltage electrode of the power source, the first conductive ring 7 has a certain width, which is helpful for sufficient contact with the transparent electrode 4 and stable connection with the low-voltage electrode of the power source.

[0093] b19. [Position of conductive ring: the top of transparent electrode 4 coincides with the top of first conductive ring 7]. Reason: The first conductive ring 7 is a connecting component connecting transparent electrode 4 and the low-voltage pole of the power supply. Since it is opaque and its resistance is much lower than that of transparent electrode 4, its position should be as far away as possible from the rod-shaped electrode 5 connected to the positive pole of the power supply to avoid blocking the implant or affecting discharge. To ensure a stable connection, the top of transparent electrode 4 coincides with the center of first conductive ring 7. Liquid metal is evenly applied to the contact position between first conductive ring 7 and transparent electrode 4 to reduce contact resistance.

[0094] b20. [Types of transparent insulating materials: PMMA / PS / PC, PMMA is preferred].

[0095] b21. [Amount of transparent insulating material to be sprayed: Since it is sprayed manually, it cannot be measured accurately. The best method is to spray evenly to achieve complete coverage without any paint flow].

[0096] b22. [The drying temperature of transparent insulating material is 0-100℃, preferably 60℃].

[0097] b23. [Drying time of transparent insulating material 0-24h, preferably 12h]. Reason: The purpose of using transparent insulating material is to isolate the transparent electrode 4 from the outside air, to prevent oxidation or corrosion caused by external oxygen or water vapor, to prevent the transparent electrode 4 from failure, and to extend its service life. At the same time, the electrode is isolated from the outside world to avoid the possible risk of electric shock. The above-mentioned types, dosages, drying temperatures, and drying times are selected according to needs in actual applications.

[0098] In this embodiment, the rod-shaped electrode 5 is used as the inner electrode of the "needle" of the "needle-ring" type coaxial dielectric barrier discharge. The rod-shaped electrode 5 is a copper column with a length of 15 mm and a diameter of 4.8 mm, and is fixed to the center of the inner side of the glass tube 1 through the second conductive ring 8 at the lower end of the glass tube 1. When the implant is treated, it is inverted above the high-voltage electrode in the tube and close to the rod-shaped electrode 5. The second conductive ring 8 leads out a wire connected to the high-voltage pole of the power supply. At the same time, silicone rubber and polytetrafluoroethylene materials are used on the outside of the second conductive ring 8 for sealing and insulation.

[0099] Among them, the protection range and preferred value of each parameter are:

[0100] c1. [Diameter of rod-shaped electrode 5: 1-5 mm, preferably 4.8 mm].

[0101] c2. [Length of rod-shaped electrode 5: 5-50 mm, preferably 15 mm].

[0102] Here are the reasons:

[0103] Diameter: Since zirconium oxide material is non-metallic, it is impossible to use the implant itself as an electrode to excite plasma like traditional treatment devices. Therefore, it is necessary to design the "needle" rod-shaped electrode 5 in the "needle-ring" configuration according to the shape of the implant. The excited plasma can completely and evenly cover the surface of the implant. The discharge field strength at the tip of the traditional needle electrode is greater, and it is easier to excite plasma, but the excited plasma mostly acts on the end of the implant, and it is difficult to cover the threaded part of the implant in the tube. Therefore, the diameter of the rod-shaped electrode 5 is increased to be larger than the diameter of the implant. When the implant is placed on the copper column and begins to be processed, it can be ensured that the range of the generated plasma can cover the threaded part of the side of the implant. At the same time, the air gap distance between the outer side of the electrode and the inner side of the glass tube 1 is reduced as much as possible to increase the excitation intensity. In order to make the excited plasma as uniform as possible, the coaxiality of the rod-shaped electrode 5 and the glass tube 1 should be increased as much as possible.

[0104] Length: The rod-shaped electrode 5 also needs to coordinate with the transparent electrode 4 in terms of size and position. The implementation plan is that the distance between the top of the rod-shaped electrode 5 and the bottom of the glass tube 1 needs to be greater than the distance between the bottom of the transparent electrode 4 and the bottom of the glass tube 1. The purpose is to reduce the distance between the two electrodes and reduce the electrical parameters (such as power and voltage) required to excite and maintain the plasma. Under the same excitation effect, lower electrical parameter conditions help to reduce the temperature of the device and the implant and extend the service life of the device. At the same time, when the distance between the top of the rod-shaped electrode 5 and the bottom of the glass tube 1 is greater than the distance between the bottom of the transparent electrode 4 and the bottom of the glass tube 1, the implant is completely wrapped by the electrode, which is conducive to the generated plasma covering the threaded part on the side of the implant.

[0105] In this embodiment, the vacuum pump 3 is AD6KEEDC24SSV, Yuanxun Intelligent Technology (Shanghai) Co., Ltd., and its function is to maintain the working pressure in the device at about -94 kPa during the treatment process. The working pressure of the vacuum pump 3 is -80 to -100 kPa, preferably -95 kPa, for the following reasons:

[0106] The gas pressure has a significant impact on plasma excitation. As the gas pressure decreases, the free path of the plasma increases and the collision frequency decreases, making it easier to increase the energy of the electrons and the excitation intensity. The experiment shows that under the same voltage output voltage, the lower the gas pressure in the glass tube 1, the higher the power output power, and the better the effect of exciting the plasma. Taking the power output frequency of 35khz and the power input voltage of 75V as an example, the gas pressure in the tube (kPa) and the actual output power of the power supply (W) are: ①-84kPa, 4.13W; ②-86kPa, 4.45W; ③-88kPa, 4.45W; ④-90kPa, 5.09W ⑤-92kPa, 5.2W; ⑥-94kPa, 5.43W. For other specific data tables under different working conditions, see Appendix 1 and Appendix 2.

[0107] In this embodiment, the plasma power supply 6 is a CTP-2000K high voltage AC power supply from Nanjing Suman Plasma Co., Ltd., with a maximum output voltage of 30KV (peak-to-peak value) and a maximum output frequency of 50KHz.

[0108] The plasma power supply 6 is the core component for exciting plasma. The type and performance of the power supply directly determine the plasma excitation situation. According to the basic principles of plasma physics, the higher the output frequency and the higher the output voltage of the power supply, the easier it is to excite the plasma, but correspondingly, the more expensive the power supply is. Considering the plasma excitation demand and price cost, this device uses a high-frequency (output frequency: kilohertz level) high-voltage (output voltage: kilovolt level) AC power supply to excite plasma.

[0109] After selecting the power type and the maximum output frequency point of the power supply, the following rules apply: the input voltage of the power supply remains unchanged, and the closer the output frequency of the power supply is to the maximum output frequency point of the power supply, the higher the output voltage of the power supply. The output frequency of the power supply remains unchanged, and the higher the input voltage of the power supply, the higher the output voltage of the power supply. The higher the output voltage of the power supply, the better the plasma excitation. The longer the processing time, the better the processing effect, but the temperature will continue to rise.

[0110] The power supply output frequency should be selected at the maximum output frequency point of the power supply, and the power supply output voltage should be as large as possible. However, the experiment found that excessively high electrical parameters will cause the transparent electrode 4 material and the implant to heat up rapidly during the plasma excitation process (90°C can be reached after 30s of treatment), which is difficult to control. Although the square resistance of the transparent electrode 4 has been as low as 30-40Ω / □, the transparent electrode 4 is a nanosilver wire network because of its conductive structure. High temperature will cause the transparent electrode 4 to age rapidly. The high temperature generated by excessively high voltage at the location where the network node resistance is large is also likely to cause the nanosilver wire network to break and lose conductivity. In actual use, the continuous treatment time should not exceed 180s, otherwise the temperature will be too high, and it must be treated multiple times before the temperature drops to room temperature before it can be used again. Correspondingly, when selecting the treatment voltage, too high a treatment voltage should not be used to avoid heating. At 35kHz / 65kHz, the power supply output voltage needs to be controlled to be less than 9.5kV. Therefore, lower electrical parameters are used in the actual treatment process to reduce the heating rate by extending the treatment time and improve the hydrophilic modification treatment effect. For specific power supply output power and electrical parameter change data tables, please see Appendix 1 and Appendix 2.

[0111] Table 1: Relationship between air pressure and electrical parameters at 35kHz power output frequency

[0112]

[0113]

[0114]

[0115] Table 2: Relationship between air pressure and electrical parameters at 65kHz power output frequency

[0116]

[0117]

[0118]

[0119] Among them, the protection range and preferred value of each parameter are:

[0120] d1. [Power output frequency: 0-100kHz, where the maximum output frequency of the power supply is about 50Hz; 35kHz and 65kHz are preferred]. Reason: Considering the plasma excitation needs and price cost, the device uses high-frequency (output frequency: kilohertz level) alternating current to excite plasma. The power input voltage remains unchanged, and the closer the power output frequency is to the maximum output frequency of the power supply, the higher the power output voltage and the better the treatment effect. However, excessively high electrical parameters will cause the transparent electrode 4 material and the implant to heat up rapidly during the plasma excitation process, which is difficult to control. The power supply used in this device is an adjustable frequency power supply, so in actual operation, a frequency that can stably excite the plasma that is far away from the maximum output frequency of the power supply is preferred to appropriately reduce the electrical parameters. For a fixed frequency power supply, since the higher the frequency, the easier it is for the electrons in the plasma to absorb energy in the electric field and oscillate in the electric field, the power output frequency can be selected as a higher frequency in the kilohertz level.

[0121] d2. [Peak-to-peak value of power supply output voltage: 1-10kV, preferably 5kV]. Reason: Considering the plasma excitation requirements and price cost, the device uses high-voltage (output voltage: kilovolt level) AC to excite plasma. The power supply output frequency remains unchanged. The higher the power supply input voltage, the higher the power supply output voltage. The higher the power supply output voltage, the better the plasma excitation. Similarly, high electrical parameters will cause the transparent electrode 4 material and the implant to heat up rapidly during the plasma excitation process, which is difficult to control. Therefore, the electrical parameters can be appropriately reduced to reduce the temperature.

[0122] d3. [Treatment time: 0-120s, preferably 60s]. Reason: The longer the treatment time, the more active substances are produced in the plasma, the more complete the interaction between the plasma and the implant, and the better the treatment effect. However, as the treatment time increases, heat will continue to accumulate at the transparent electrode 4, and the temperature of the transparent electrode 4 will continue to rise. Excessively high temperatures will cause the nanosilver wire network to melt and break at the locations where the resistance of the overlapping nodes is large, thereby losing conductivity. In actual use, the continuous treatment time must not exceed 180s, otherwise the temperature will be too high, and it must be treated multiple times before the temperature drops to room temperature before it can be used again. However, if the treatment time is too short, the plasma treatment is insufficient and a better treatment effect cannot be achieved.

[0123] d4. [Upper limit of treatment temperature: not more than 55℃, preferably 40℃]. Reason: The implant treatment process is chairside and requires immediate implant surgery after treatment. The temperature of the implant must not be too high to avoid scalding the patient. Considering the size of the zirconia implant, the thermal conductivity of the zirconia material, the convection heat transfer coefficient of the air, and the actual power of the excited plasma, the upper limit of the treatment temperature is set at 55℃.

[0124] Taking the surface hydrophilic modification of zirconium oxide implants as an example, the working principle is explained step by step in chronological order:

[0125] e1. Initial state: there is no implant in the glass tube 1, the pneumatic connector 2 is connected to the glass tube 1, the vacuum pump 3 is not working, the vacuum gauge 9 reads 0, the plasma power supply 6 is not working, and there is no plasma.

[0126] e2. Preparation state: Place the zirconia implant into the glass tube 1: Disconnect the connection between the pneumatic connector 2 and the glass tube 1, place the zirconia implant upside down into the glass tube 1 from the connection, and then reconnect the pneumatic connector 2 and the glass tube 1, leaving the rest of the body unchanged.

[0127] e3. Vacuuming: After checking that the system is sealed, turn on the vacuum pump 3 until the reading on the vacuum gauge 9 reaches -95 kPa and remains unchanged.

[0128] e4. Plasma treatment: Turn on the plasma power supply 6, adjust the output frequency to 35kHz, the peak-to-peak value of the power supply output voltage to 5kV, the peak-to-peak value of the output current to about 45mA, the power supply output power to about 5.5W, the treatment time to 60s, and the maximum temperature of the device to <40°C. During the treatment, blue-purple plasma is generated inside the glass tube 1 and covers the implant.

[0129] e5. End of treatment: turn off the plasma power supply 6, disconnect the pneumatic connector 2 from the glass tube 1, and take the zirconia implant out of the glass tube 1 from the connection for later use. At this point, the implant treatment is complete. After the implant is taken out, reconnect the pneumatic connector 2 to the glass tube 1 to restore it to its initial state. The treatment process ends.

[0130] In this embodiment, a simple method for judging the effect of the hydrophilic modification treatment is as follows: invert the treated implant, and contact the top end face with the test liquid (which should be artificial blood, but red ink is used instead in the actual experiment). After the hydrophilic modification of the implant surface, the test liquid will climb upward along the thread due to the capillary effect at the side thread. The hydrophilic modification effect of the implant is judged by observing the number of turns of the test liquid rising at the side thread of the implant and the average time taken for each thread to rise: the more turns the thread rises and the less time it takes, the better the hydrophilicity. Through experiments, it is found that when the air pressure and the treatment time remain unchanged, as the input voltage of the power supply increases, the actual output power of the power supply increases, the number of turns of the test liquid rising at the side thread of the implant first increases and then decreases, and the average time taken for each thread to rise first shortens and then lengthens. This is because as the actual output power of the power supply increases, the plasma excitation is better, the interaction between the implant and the plasma is more sufficient, and the hydrophilic modification effect is better. However, when the power is too large, the plasma is excited too violently, the plasma temperature rises, and the implant temperature rises, so that the hydrophilicity of the implant may be damaged to a certain extent by the higher temperature during the treatment process. Specific experimental data are shown in Appendix 3.

[0131] Among them, the relationship between electrical parameters and hydrophilicity is shown in Appendix 3:

[0132] Table 3: Relationship between electrical parameters and hydrophilicity

[0133]

[0134]

[0135] In summary, the present invention excites plasma by reducing the gas pressure, so that the processing system can directly excite the air in the glass tube 1 to generate plasma, without the need for additional gas cylinders, greatly reducing the hardware size, and broadening the use scenario to the desktop level; no rare gas is needed as the working gas, which can greatly reduce the processing cost; because the total amount of gas excited in the glass tube 1 decreases after the gas pressure is reduced, the power required for exciting the gas is reduced, and the processing temperature is greatly reduced to the room temperature level, without the need for additional heat dissipation, meeting the doctor's need for immediate treatment at the chair before the operation. The present invention forms a "needle-ring" electrode structure by using a transparent electrode 4 and a rod-shaped electrode 5, and adjusts the position parameters and size parameters of the two electrodes so that the transparent electrode 4 as a "ring" and the rod-shaped electrode 5 as a "needle" cooperate with each other, which can directly excite plasma, without the need to use a metal implant as an electrode to excite the implant like a traditional device, and can then process zirconia implants and other related dental non-metallic materials; by completely wrapping the implant between the two electrodes, the generated plasma can more evenly cover the entire implant, achieving a better treatment effect. The present invention solves the problem that conventional transparent electrode 4 materials cannot generate plasma due to substandard electrical properties or their performance deteriorates seriously after long-term use. The present invention can generate plasma stably for a long time under working conditions. Due to the transparency of the transparent electrode 4, relevant parameters can be monitored in real time during the process of generating plasma. By using detection means such as a spectrometer and an infrared thermal imager, data such as plasma active substances and device temperature can be detected in real time during the hydrophilic activation treatment. Closed-loop control is performed while ensuring thermal safety, and electrical parameters are adjusted in real time to ultimately obtain optimal parameters. The treatment process is intuitively and visually presented, which minimizes the distrust of doctors and patients in implant treatment. The manufacturing process of the transparent electrode 4 is simple and the manufacturing cost is extremely low. The transparent electrode 4 of the present invention is sprayed on the outside of the glass tube 1, and its function is to connect to the low-voltage pole of the power supply and generate plasma as a low-voltage pole. The position and size of the transparent electrode 4 are closer to the rod-shaped "needle" electrode than the existing device, and even partially overlap. It is helpful to excite plasma with lower power, and at the same time, the generated plasma can completely cover the implant. The present invention increases the diameter of the "needle"-shaped rod-shaped electrode 5 to be larger than the diameter of the implant, so as to ensure that the range of plasma generation can cover the threaded part on the side of the implant. The air gap distance between the outer side of the electrode and the inner side of the glass tube 1 can be reduced to improve the excitation intensity. The coaxiality between the rod-shaped electrode 5 and the glass tube 1 can be improved to make the plasma generated by excitation in the glass tube 1 as uniform as possible. The distance between the top of the rod-shaped electrode 5 and the bottom of the glass tube 1 needs to be greater than the distance between the bottom of the transparent electrode 4 and the bottom of the glass tube 1. Reducing the distance between the two electrodes reduces the electrical parameters (such as power and voltage) required for exciting and maintaining plasma, which helps to reduce the temperature of the device and the implant and prolong the service life of the device.

[0136] Example 2

[0137] Embodiment 2 of the present invention also provides a method for preparing a transparent electrode 4 of a zirconium oxide implant surface modification system, comprising the following steps:

[0138] S1, cleaning the glass substrate using a washing liquid;

[0139] S2, performing jet treatment on the cleaned glass substrate using plasma;

[0140] S3, preparing a nano silver wire raw material solution, wherein the diameter of the nano silver wire in the nano silver wire raw material solution is 40-300nm; the concentration of the nano silver wire raw material solution is 5-20mg / ml; diluting the nano silver wire raw material solution to a concentration range of 0-10mg / ml;

[0141] S4, spraying the diluted silver nanowire raw material solution onto the glass substrate after the jet treatment;

[0142] S5, performing plasma jet treatment on the nano silver wire layer on the glass substrate after spraying the nano silver wire raw material solution;

[0143] S6, preparing a liquid metal solution, diluting the liquid metal raw material in the solution to 0-3 mg / ml, and performing ultrasonic mixing treatment on the diluted liquid metal solution;

[0144] S7, spraying the diluted liquid metal solution onto the nano silver wire layer on the glass substrate after the plasma jet treatment;

[0145] S8, placing the glass substrate sprayed with the diluted liquid metal solution upside down above the liquid surface of an open container containing hydrochloric acid for treatment, and after treatment, placing the glass substrate in a drying oven for drying to form an electrode;

[0146] S9, spraying a transparent protective material for a circuit board onto the electrode on the surface of the dried glass substrate, and drying the sprayed transparent protective material for a circuit board to form a transparent electrode 4.

[0147] In this embodiment, in step S1, according to different substrate materials, a conventional cleaning method is selected, such as mechanical scrubbing, ultrasonic cleaning machine cleaning, etc., and the cleaning liquid can be deionized water, ethanol, etc. The selected substrate material is glass. The cleaning method used is ultrasonic cleaning machine cleaning, and the washing liquid is deionized water.

[0148] In this embodiment, in step S2, the purpose is to use a low-temperature plasma jet to uniformly scan and process the substrate, remove pollutants on the substrate and perform hydrophilic modification on the substrate. An appropriate processing speed is selected according to plasma parameters, and the plasma parameters are as follows:

[0149] f1) Gas selection: argon / helium / oxygen / mixed gas, or other gases that can excite plasma;

[0150] f2) Power source type selection: microwave source / AC source / RF source / DC pulse source / hybrid power source;

[0151] f3) Air flow parameters: gas flow / mixed gas ratio;

[0152] f4) Power supply parameters: output frequency / output voltage / output current / output power;

[0153] f5) Electrode structure: single needle type / needle ring type / ring ring type;

[0154] f6) Jet shape: length / diameter / temperature)

[0155] Specifically, the selected plasma parameters are: gas selection: helium (purity 99%) and oxygen (purity 99%) mixed gas; power type selection: AC source; gas flow parameters: gas flow 1-10slm, preferably 5slm / mixed gas ratio He:O2=100:0-100:100, preferably He:O2=100:1; power supply parameters: output frequency 0-100kHz, preferably 35kHz / output voltage 0-20kV, preferably 6kV / output current 0-0.5A, preferably 0.21A / output power 0-50W, preferably 8W); electrode structure: ring type; jet shape: length 5cm / diameter 6mm / temperature <45°C). The processing speed selected in this embodiment is 0-5cm / s, preferably 0.5cm / s.

[0156] In this embodiment, in step S3, the purpose is to dilute the nanosilver wire raw material solution to the optimal concentration range. The nanosilver wire here is the abbreviation of metal nanowire materials (micro-nano one-dimensional conductive materials in a broad sense, such as one-dimensional carbon nanotubes) and their solutions, and common ones include nanosilver wires, nanocopper wires, etc. The parameters that need to be controlled are: the diameter / length of the nanosilver wires in the nanosilver wire raw material solution; the type of dispersant for the nanosilver wires: water / ethanol / isopropanol; the concentration of the nanosilver wire raw material solution; the optimal concentration range of the nanosilver wire after dilution.

[0157] Specifically, the parameters selected are: the diameter of the nanosilver wire in the nanosilver wire raw material solution is 40-300nm, preferably 50nm / length is 10-200μm, preferably 100-150μm; the core is to select nanowires with a large aspect ratio; the type of dispersant for the nanosilver wire: isopropanol; the concentration of the nanosilver wire raw material solution is 5-20mg / ml, preferably 10mg / ml; the optimal concentration range of the nanosilver wire after dilution is 0-10mg / ml, preferably 0.5mg / ml.

[0158] In this embodiment, in step S4, the purpose is to transfer the prepared nano silver wire solution to the substrate. The parameters that need to be controlled are: transfer method: spraying / spin coating / deposition / magnetron sputtering, etc.); if ordinary spray gun is used for spraying, the spray carrier gas: gas type / flow rate; spraying speed; spraying nano silver wire solution amount need to be controlled.

[0159] Specifically, the parameters selected are: transfer method: ordinary spray gun spraying; spray carrier gas: nitrogen or compressed air, preferably nitrogen (anti-oxidation nanosilver wire), pressure 4 bar; spray speed is manual operation, specifically to make the nanosilver wire solution spray out in a mist, and it is better to evaporate the solution immediately after spraying it to the substrate without leaving any liquid stains; the amount of nanosilver wire solution sprayed is 0-1ml / cm 2 , preferably 0.5 ml / cm 2 ).

[0160] In this embodiment, in step S5, the purpose is to remove the highly surface active polyvinyl pyrrolidone (PVP) remaining in the nano silver wire layer to enhance the conductivity of the nano silver wire. The plasma parameters that need to be controlled are: gas selection: argon / helium / oxygen / mixed gas, or other gases that can excite plasma; power source type selection: microwave source / AC source / RF source / DC pulse source / mixed power source; gas flow parameters: gas flow / mixed gas ratio; power supply parameters: output frequency / output voltage / output current / output power; electrode structure: single needle type / needle ring type / ring ring type; jet morphology: length / diameter / temperature. The core is to adjust the processing speed according to the plasma parameters and monitor the temperature of the nano silver wire layer.

[0161] Specifically, the selected plasma parameters are: gas selection: a mixture of helium (purity 99%) and oxygen (purity 99%); power source type selection: AC source; gas flow parameters: gas flow 1-10slm, preferably 5slm / mixed gas ratio He:O2=100:0-100:100, preferably He:O2=100:1; power supply parameters: output frequency 0-100kHz, preferably 35kHz / output voltage 0-20kV, preferably 6kV / output current 0-0.5A, preferably 0.21A / output power 0-50W, preferably 8W; electrode structure: ring type; jet morphology: length 5cm / diameter 6mm / temperature <45°C. The processing speed selected in this embodiment is 0-5cm / s, preferably 0.5cm / s. The temperature of the monitored nano silver wire shall not be higher than 60°C.

[0162] In this embodiment, in step S6, the purpose is to dilute the liquid metal raw material in the solution to an optimal concentration range. The parameters that need to be controlled are: liquid metal type: gallium / indium or its alloy; liquid metal element ratio; liquid metal optimal concentration range.

[0163] Specifically, the parameters selected are: liquid metal type: gallium-indium alloy; liquid metal element ratio gallium:indium = 0:1-1:0, preferably gallium:indium = 3:1; liquid metal optimal concentration range 0-3mg / ml, preferably 1mg / ml. The process of preparing liquid metal is: 60mg of liquid metal is dispersed in 20ml of isopropanol, and then ultrasonicated at a power of 600W for 20 minutes. After ultrasonication, a gray suspension is obtained, which is further diluted to 1mg / ml with isopropanol.

[0164] In this embodiment, in step S7, the purpose is to transfer the prepared liquid metal solution to the nano silver wire layer. The parameters to be controlled are:

[0165] Transfer method: spraying / spin coating / deposition / magnetron sputtering, etc. If ordinary spray gun is used for spraying, it is necessary to control the type / flow rate of the spray carrier gas; spraying speed; amount of liquid metal solution sprayed).

[0166] Specifically, the selected parameters are:

[0167] Transfer method: spraying with ordinary spray gun; spraying carrier gas: nitrogen or compressed air, preferably nitrogen, pressure 4 bar; spraying speed is difficult to quantify due to manual operation, specifically, the nano silver wire solution is sprayed in a mist form, and it is best if the solution can evaporate and dry immediately after spraying to the substrate without leaving any liquid stains; the amount of liquid metal solution sprayed is 0-1ml / cm 2 , preferably 0.2 ml / cm 2 .

[0168] In this embodiment, in step S8, the substrate sprayed with liquid metal is inverted above the liquid surface of an open container containing hydrochloric acid for treatment, and the substrate is placed in a drying oven for drying after treatment. The purpose of this step: hydrochloric acid vapor treatment is to break the oxidation shell of the liquid metal microcapsule sprayed on the surface of the nanosilver wire and release the internal fluid liquid metal. The liquid metal covers and hybridizes with the nanosilver wire network below to form a membrane structure. The purpose of drying is to remove excess hydrochloric acid vapor and water to prevent the nanosilver wire from reacting with hydrochloric acid to form silver chloride aggregates and causing the nanosilver wire to break. The parameters that need to be controlled in this step are: hydrochloric acid concentration; treatment time; distance between the electrode and the hydrochloric acid liquid surface during hydrochloric acid treatment; drying temperature; drying time.

[0169] Specifically, the selected parameters are hydrochloric acid concentration: 0-50%, preferably 36%-38%; treatment time 0-30s, preferably 10s; the distance between the electrode and the hydrochloric acid liquid surface during hydrochloric acid treatment is 0-10cm, preferably 1cm; drying temperature 0-100°C, preferably 35°C; drying time 0-10h, preferably 4h.

[0170] In this embodiment, in step S9, the purpose is to spray the transparent insulating material onto the surface of the transparent electrode 4. The parameters that need to be controlled are: type of transparent insulating material: PMMA / PS / PC; spraying amount; and environmental humidity during spraying.

[0171] Specifically, the parameters selected are: type of transparent insulating material: PMMA; spraying amount: manual spraying, so it is impossible to measure accurately, and it is best to spray evenly and completely cover without paint flow; environmental humidity during spraying: relative humidity 0-100%, preferably 20%. At the same time, drying the protective material allows the protective material to dry quickly. The parameters that need to be controlled are: drying temperature; drying time. The parameters selected in this embodiment are: drying temperature 0-100°C, preferably 60°C; drying time 0-24h, preferably 12h.

[0172] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A zirconia implant surface modification treatment system, characterized in that: It includes a glass tube, a pneumatic joint, a vacuum pump, a transparent electrode, a rod electrode and a plasma power supply; The upper end of the glass tube is connected to the pneumatic joint, and the pneumatic joint is connected to the vacuum pump through a pipeline, and the vacuum pump is used to adjust the working air pressure inside the glass tube; a zirconium oxide implant is arranged inside the glass tube; The transparent electrode is sprayed on the outer wall of the glass tube, and the rod-shaped electrode is fixed on the inner center of the lower end of the glass tube; the zirconia implant is inverted above the rod-shaped electrode and is closely attached to the rod-shaped electrode; The transparent electrode completely wraps the zirconia implant in the spraying area outside the glass tube, and the transparent electrode also wraps the rod-shaped electrode of a preset length in the spraying area outside the glass tube; The transparent electrode is electrically connected to the low voltage pole of the plasma power supply, the rod-shaped electrode is electrically connected to the high voltage pole of the plasma power supply, and the plasma power supply excites plasma through the transparent electrode and the rod-shaped electrode to modify the surface of the zirconia implant.

2. A zirconium oxide implant surface modification treatment system according to claim 1, characterized in that: The glass tube is made of quartz glass with a dielectric constant of 4-20; The length of the glass tube is 5-15 cm, the inner diameter of the glass tube is 4-6 mm, and the thickness of the glass tube is 1-3 mm.

3. A zirconium oxide implant surface modification system according to claim 1, characterized in that: A first conductive ring is provided at the electrical connection between the transparent electrode and the low voltage pole of the plasma power supply, and the center of the first conductive ring coincides with the center of the top end of the transparent electrode; A second conductive ring is provided at the electrical connection between the transparent electrode and the high voltage pole of the plasma power supply, and the outer side of the second conductive ring is sealed and insulated with silicone rubber and polytetrafluoroethylene materials.

4. The zirconia implant surface modification system according to claim 1, characterized in that: The transparent electrode is an electrode made of nano silver wire and liquid metal covered with PMMA / PS / PC transparent insulating material.

5. The zirconia implant surface modification system according to claim 1, characterized in that: The rod-shaped electrode adopts a copper column, the diameter of the rod-shaped electrode is 1-5 mm, and the length of the rod-shaped electrode is 5-50 mm.

6. A zirconium oxide implant surface modification system according to claim 5, characterized in that: A first distance between the top end of the rod-shaped electrode and the bottom end of the glass tube is greater than a second distance between the bottom end of the transparent electrode and the bottom end of the glass tube.

7. The zirconia implant surface modification system according to claim 1, characterized in that: The working pressure of the vacuum pump is -80 to -100 kPa, and a vacuum gauge is connected to the pipeline between the pneumatic joint and the vacuum pump, and the vacuum gauge is used to indicate the working pressure inside the glass tube; The output frequency of the plasma power supply is 0-100kHz, and the output voltage peak value of the plasma power supply is 1-10kV.

8. A method for preparing a transparent electrode of a zirconium oxide implant surface modification system, characterized in that: The following steps are involved: cleaning the glass substrate using a washing liquid; Using plasma to perform jet treatment on the cleaned glass substrate; Prepare a nano silver wire raw material solution, wherein the diameter of the nano silver wire in the nano silver wire raw material solution is 40-300nm; the length of the nano silver wire in the nano silver wire raw material solution is 10-200μm; the concentration of the nano silver wire raw material solution is 5-20mg / ml; dilute the nano silver wire raw material solution to a concentration range of 0-10mg / ml; Spraying the diluted silver nanowire raw material solution onto the glass substrate after the jet treatment; Performing plasma jet treatment on the nano silver wire layer on the glass substrate after spraying the nano silver wire raw material solution; preparing a liquid metal solution, diluting the liquid metal raw material in the solution to 0-3 mg / ml, and subjecting the diluted liquid metal solution to ultrasonic mixing; Spraying the diluted liquid metal solution onto the nano silver wire layer on the glass substrate after the plasma jet treatment; The glass substrate sprayed with the diluted liquid metal solution is placed upside down above the liquid surface of an open container containing hydrochloric acid for treatment, and after treatment, the glass substrate is placed in a drying oven for drying to form an electrode; A transparent protective material for a circuit board is sprayed onto the electrode on the surface of the dried glass substrate, and the sprayed transparent protective material for the circuit board is dried to form a transparent electrode.

9. The method for preparing a transparent electrode of a zirconium oxide implant surface modification system according to claim 8, characterized in that: The liquid metal is a gallium-indium alloy; the liquid metal element ratio of gallium:indium=0:1-1:0; the dilution solution of the liquid metal raw material is isopropanol; Spraying liquid metal solution dosage 0-1ml / cm 2 .

10. The method for preparing a transparent electrode of a zirconium oxide implant surface modification system according to claim 8, characterized in that: The concentration of the hydrochloric acid is 0-50%, and the treatment time is 0-30s; the distance between the electrode and the hydrochloric acid liquid surface during the hydrochloric acid treatment is 0-10cm; the drying temperature after the hydrochloric acid treatment is 0-100°C, and the drying time is 0-10h; The transparent protective material of the circuit board adopts PMMA / PS / PC transparent insulating material.